Using lean six sigma to evaluate the efficiency of gold processing plants - Fernandes, Nicholas (Stellenbosch : Stellenbosch University, 2025)
Fernandes, N. 2025. Using Lean Six Sigma to evaluate the efficiency of gold processing plants. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/512a32ed-d8f9-43d4-b1fe-e9c0315acbeb